(untitled) (Progressive Agriculture, 2016)
Hemorrhagic septicemia (HS) is an acute septicemic disease that primarily affects cattle and buffaloes. The disease is caused by Pasteurella multocida sero types B:2 and E:2. The objective of this study was to isolate P. multocida from clinical cases and to confirm its identity using polymerase chain reaction (PCR) based approach. Clinical samples of two suspected cases of haemorrhagic septicemia of cattle and buffalo from Mymensingh and Rajshahi districts respectively were collected. Two isolates were isolated from these suspected cases and primarily identified as P. multocida based on morphological study, staining properties, and cultural and biochemical characteristics. The isolates were confirmed initially as P. multocida at genus level by PCR using genus specific primers. Later, the isolates were confirmed as P. multocida type B, the causal agent of haemorrhagic septicemia, by PCR with primers specific for P. multocida type B. These isolated organisms can be used as vaccine candidate for the production of effective vaccine against haemorrhagic septicemia. Progressive Agriculture 27 (2): 175-179, 2016